Inventory of Pests and Diseases Intensity on 10 Bambara Groundnut (Vigna subterranea (L.) Verdc.) Lines in The Dryland of Madura, Indonesia, during The Dry Season - Fatimah, Siti; Muafalah, Siti; Nurholis, Nurholis; Djunaedy, Achmad (Universitas Trunojoyo Madura, 2022)
Landraces breeding scheme of bambara groundnut from various regions of Indonesia since 2012 provides several potential lines which are uniform, high yielding and drought-tolerant. Evaluation of resistance to pests and diseases is aimed to select potential lines which are resistant to pests and diseases and potential for development in Madura dry land during the dry season. The present study used descriptive method through field observation technique on 10 selected potential lines of Bambara groundnut. The results showed that there were 5 (five) types of pests and 4 types of diseases found in bambara groundnut crops planted during the dry season in Bangkalan Regency of Madura. The pests attacking more than 25% per plot were aphids, ladybugs and grasshoppers. A symptom of pathogen attacking more than 25% per plot were Bean common mosaic virus and soybean common mosaic virus. The GSG 1.1.1 potential line had the lowest pest attack and the BBL 2.1.1 potential line had the lowest disease incidence.